Cross national study of injury and social determinants in adolescents. Issue 4 (4th August 2005) - Pickett, W; Molcho, M; Simpson, K; Janssen, I; Kuntsche, E; Mazur, J; Harel, Y; Boyce, W F
Abstract : Objectives: To compare estimates of the prevalence of injury among adolescents in 35 countries, and to examine the consistency of associations cross nationally between socioeconomic status then drunkenness and the occurrence of adolescent injury. Design: Cross sectional surveys were obtained from national samples of students in 35 countries. Eight countries asked supplemental questions about injury. Setting: Surveys administered in classrooms. Subjects: Consenting students (n = 146 440; average ages 11–15 years) in sampled classrooms. 37 878 students (eight countries) provided supplemental injury data. Exposure measures: Socioeconomic status (material wealth, poverty) and social risk taking (drunkenness). Outcome measures: Specific types and locations of medically treated injury. Results: By country, reports of medically treated injuries ranged from 33% (1060/3173) to 64% (1811/2833) of boys and 23% (740/3172) to 51% (1485/2929) of girls, annually. Sports and recreation were the most common activities associated with injury. High material wealth was positively (OR>1.0; p<0.05) and consistently (6/8 countries) associated with medically treated and sports related injuries. Poverty was positively associated with fighting injuries (6/8 countries). Drunkenness (social risk taking) was positively (p<0.01) and consistently (8/8 countries) associated with medically treated, street, and fighting injuries, but not school and sports related injuries. Conclusion: The high prevalence of adolescent injury confirms its importance as a health problem. Social gradients in risk for adolescent injury were illustrated cross nationally for some but not all types of adolescent injury. These gradients were most evident when the etiologies of specific types of adolescent injury were examined. Prevention initiatives should focus upon the etiologies of specific injury types, as well as risk oriented social contexts.